The wife, the maid, and the mistress : a novel - Lawhon, Ariel (New York : Anchor Books, a division of Random House LLC, 2014)
Stella Crater, the judge's wife, is the picture of propriety. Ritzi, a leggy showgirl with Broadway aspirations, thinks moonlighting in the judge's bed is the quickest way off the chorus line. Maria Simon, the dutiful maid, has the judge to thank for her husband's recent promotion to detective in the NYPD. On a sultry summer night, as rumors circulate about the judge's involvement in wide-scale political corruption, the Honorable Joseph Crater steps into a cab and disappears without a trace. Or does he? After 39 years of necessary duplicity, Stella Crater is finally ready to reveal what she knows ...
"With new epilogue"--Cover.
Keywords: Crater, Joseph Force, -- 1889- -- Fiction; Judges -- New York (State) -- New York -- Fiction; Missing persons -- Fiction; Biographical fiction; Historical fiction; Mystery fiction